Generalized SEIR Epidemic Model for COVID-19 in a Multipatch Environment. (17th December 2021) - Meng, Lan; Zhu, Wei
Abstract : In this paper, an n -patch SEIR epidemic model for the coronavirus disease 2019 (COVID-19) is presented. It is shown that there is unique disease-free equilibrium for this model. Then, the dynamic behavior is studied by the basic reproduction number. The transmission of COVID-19 is fitted based on actual data. The influence of quarantined rate and population migration rate on the spread of COVID-19 is also discussed by simulation.